2010
DOI: 10.1585/pfr.5.s2054
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Diamagnetic Signal in Current-Free Stellarators

Abstract: The toroidal magnetic flux through the plasma column is calculated analytically for current-free stellarators of arbitrary geometry without assumptions on the plasma shape, aspect ratio, etc. This is done with accuracy sufficient for extracting the contribution due to the finite plasma pressure from this flux. The final result is a formula relating the measured diamagnetic signal with β, the ratio of the plasma pressure to the magnetic pressure. This formula is obtained assuming small β and the relative depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…where δ means the difference of the final and initial values, ( ) β a J is the 'poloidal beta' defined by ( 3) and calculated for a plasma within a toroidal tube = a const, and b is the plasma minor radius. If the wall of minor radius a w acts as a perfect conductor, the net plasma column shift ∆ b must vary as [52][53][54]…”
Section: Simulation Resultsmentioning
confidence: 99%
“…where δ means the difference of the final and initial values, ( ) β a J is the 'poloidal beta' defined by ( 3) and calculated for a plasma within a toroidal tube = a const, and b is the plasma minor radius. If the wall of minor radius a w acts as a perfect conductor, the net plasma column shift ∆ b must vary as [52][53][54]…”
Section: Simulation Resultsmentioning
confidence: 99%
“…found in [9] between the diamagnetic β values calibrated by the new method based on 3D magnetohydrodynamic (MHD) equilibrium calculations and that from a conventional method under the cylindrical and large aspect ratio plasma model. This discrepancy remains mysterious, and it looks even more puzzling in view of earlier analytical [16] and numerical [17] predictions that, for stellarators, higher order corrections to the diamagnetic flux in (1) would be small, in qualitative agreement with the statements on the toroidal corrections in [1].…”
Section: Introductionmentioning
confidence: 89%
“…In addition, the problem of δS pl detection as a quantity related to diamagnetic measurements was never addressed in theory (except several papers, see [21,32]) and experiments. However, recent studies [18] of the LHD plasma boundary change with β have demonstrated that the related δS pl (though of a different origin from that we discuss in this section) can be large enough to be detected.…”
Section: Flux-conserving Plasma Evolution and Diamagnetic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of these additional terms related to the toroidal plasma current can be minimised by arranging the DL perpendicular to the plasma axis and thus in leading order perpendicular to a possible toroidal plasma current. A detailed derivation of all these terms can be found in [12].…”
Section: Diamagnetic Loopsmentioning
confidence: 99%